Pelayanan Informasi Meteorologi Penerbangan Di Bandara Fatmawati Bengkulu - Yuke Sri Rizki (WARTA ARDHIA, 2012)
Guidelines assesment for aviation meteorological information services is expected to be useful to improve aviation meteorological information services at the airport and will directly improve aviation safety. This assessment will evaluate the guidelines for aviation meteorological information services in order to figure out the obstacles encoutered in the services and part or elements of services that need further improvements, and to make recommendations related to the aviation meteorological information services.Pengkajian pelayanan informasi meterologi penerbangan di Bandara Fatmawati Soekarno Bengkulu diharapkan dapat bermanfaat untuk meningkatkan pelayanan informasi meteorologi penerbangan di bandar udara dan secara langsung akan meningkatkan keselamatan penerbangan. Pengkajian ini akan mengevaluasi pelayanan mana yang perlu dilakukan penyempurnaan. Pada akhir analisis akan disusun suatu rekomendasi peningkatan pelayanan informasi meteorologi penerbangan dib bandar udara Fatmawati Soekarno Bengkulu.